2022
DOI: 10.1007/s00382-022-06508-6
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric pathways of the late-winter ENSO teleconnection to Europe

Abstract: The late-winter signal associated with the El Niño-Southern Oscillation (ENSO) over the European continent is unsettled. Two main anomalous patterns of sea-level pressure (SLP) can be identified: a “wave-like” pattern with two opposite-signed anomalies over Europe, and a pattern showing a single anomaly (“semi-isolated”). In this work, potential paths of the tropospheric ENSO teleconnection to Europe and their role in favoring a more wave-like or semi-isolated pattern are explored. Outputs from historical runs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Also, many studies have investigated the influence of Pacific Ocean on South Europe and Mediterranean region. ENSO is an important interannual climate variability influencing precipitation over Atlantic-Europe region [22][23][24] . Previous studies have found increased wintertime precipitation over Britain, France, and Germany during an El Niño, but decreased precipitation over Scandinavia 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, many studies have investigated the influence of Pacific Ocean on South Europe and Mediterranean region. ENSO is an important interannual climate variability influencing precipitation over Atlantic-Europe region [22][23][24] . Previous studies have found increased wintertime precipitation over Britain, France, and Germany during an El Niño, but decreased precipitation over Scandinavia 25 .…”
Section: Introductionmentioning
confidence: 99%